Diffusion of multiple information: On information resilience and the power of segregation - Nicole Tabasso (Fondazione Eni Enrico Mattei (FEEM), 2015)
We introduce two pieces of information, denoted memes, into a diffusion process in which memes are transmitted when individuals meet and forgotten at an exogenous rate. At most one meme can be transmitted at a meeting, which introduces opportunity costs in the process. Individuals differ according to which meme they find more interesting, and that is the one they transmit if they face a choice. We find that both memes survive under the same parameter values, and that relative interest is the main determinant in the number of people informed of a meme in the long run. We apply our framework to analyze the impact of segregation and find that segregation leads to polarization. Segregation also reduces the overall number of people informed in the long run. Our final set of results shows that agents are more likely to prefer segregation if their information preferences are more extreme, if they have few social contacts, or if they prefer a meme that is preferred by only a small fraction of the population.
Keywords: D83; D85; 330; Social Networks; Information Transmission; Multiple States; Segregation